2001
DOI: 10.1142/s0217751x01003974
|View full text |Cite
|
Sign up to set email alerts
|

Domain Wall World(s)

Abstract: Gravitational properties of domain walls in fundamental theory and their implications for the trapping of gravity are reviewed. In particular, the difficulties to embed gravity trapping configurations within gauged supergravity is reviewed and the status of the domain walls obtained via the breathing mode of sphere reduced Type IIB supergravity is presented.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…These walls could be realized as supersymmetric bosonic configurations. Examples of supersymmetric domain walls in D=4 N = 1 supergravity coupled to chiral matter superfields were first found and studied in [21], and recent examples within D=5 gauged supergravities were given in [10].…”
Section: Classification Of the Domain Wall Solutionsmentioning
confidence: 99%
“…These walls could be realized as supersymmetric bosonic configurations. Examples of supersymmetric domain walls in D=4 N = 1 supergravity coupled to chiral matter superfields were first found and studied in [21], and recent examples within D=5 gauged supergravities were given in [10].…”
Section: Classification Of the Domain Wall Solutionsmentioning
confidence: 99%
“…The S 7 also admits the second, squashed Einstein metric [8], yielding a vacuum with SO(5) × SO(3) gauge symmetry and N = 1 or N = 0 supersymmetry, depending on the orientation of the S 7 [9].In [1], we have shown that the well-known spontaneous (super)symmetry breaking deformation from round-to squashed-S 7 is mapped to a renormalization group flow from N = 0 or 1, SO(5) × SO(3) invariant fixed point in the UV to N = 8, SO(8) invariant fixed point in the IR. In particular, in [1], we have shown that (1) the squashing deformation corresponds to an irrelevant operator at the N = 8 superconformal fixed point and a relevant operator at the N = 1 or 0 (super)conformal fixed point, respectively, and (2) the renormalization group flow is described geometrically, as in AdS 5 supergravity [10], by a 'static' domain wall of the sort studied earlier in [11], which interpolates the two asymptotically AdS 4 spacetimes with X 7 round and squashed S 7 's.In this paper, we will be studying further known examples of Kaluza-Klein supergravity vacua and reinterpret them in terms of three-dimensional (super)conformal field theories and associated renormalization group flows. First, we will be exploring various Freund-Rubin type spontaneous compactifications on AdS 4 ×X 7 .…”
mentioning
confidence: 99%
“…In [1], we have shown that the well-known spontaneous (super)symmetry breaking deformation from round-to squashed-S 7 is mapped to a renormalization group flow from N = 0 or 1, SO(5) × SO(3) invariant fixed point in the UV to N = 8, SO(8) invariant fixed point in the IR. In particular, in [1], we have shown that (1) the squashing deformation corresponds to an irrelevant operator at the N = 8 superconformal fixed point and a relevant operator at the N = 1 or 0 (super)conformal fixed point, respectively, and (2) the renormalization group flow is described geometrically, as in AdS 5 supergravity [10], by a 'static' domain wall of the sort studied earlier in [11], which interpolates the two asymptotically AdS 4 spacetimes with X 7 round and squashed S 7 's.…”
mentioning
confidence: 99%
“…Let us consider the bosonic part of a five-dimensional supergravity theory obtained via compactification of a higher dimensional supergravity, given in the general form [26,27,[29][30][31] …”
Section: The Modelmentioning
confidence: 99%
“…Admitting that both A and scalar fiels φ, χ depend only on the fifth coordinate x, then the equation of motion for the scalar fields and the Einstein's equations read [26][27][28][29][30][31][32][33][34] …”
Section: Turning On the Gravitational Fieldmentioning
confidence: 99%